Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\frac{1}{2}x+\frac{5}{2}=\frac{7}{2}x-\frac{3}{4}\)
\(\Leftrightarrow\frac{1}{2}x+\frac{5}{2}-\frac{7}{2}x=-\frac{3}{4}\)
\(\Leftrightarrow\frac{1}{2}x-\frac{7}{2}x+\frac{5}{2}=-\frac{3}{4}\)
\(\Leftrightarrow-3x+\frac{5}{2}=-\frac{3}{4}\)
\(\Leftrightarrow-3x=-\frac{13}{4}\)
\(\Leftrightarrow x=-\frac{13}{4}:(-3)=-\frac{13}{4}:\frac{-3}{1}=-\frac{13}{4}\cdot\frac{-1}{3}=\frac{13}{12}\)
\(b,\frac{2}{3}x-\frac{2}{5}=\frac{1}{2}x-\frac{1}{3}\)
\(\Leftrightarrow\frac{2}{3}x-\frac{2}{5}-\frac{1}{2}x=-\frac{1}{3}\)
\(\Leftrightarrow\frac{2}{3}x-\frac{1}{2}x-\frac{2}{5}=-\frac{1}{3}\)
\(\Leftrightarrow\frac{1}{6}x-\frac{2}{5}=-\frac{1}{3}\)
\(\Leftrightarrow\frac{1}{6}x=\frac{1}{15}\)
\(\Leftrightarrow x=\frac{1}{15}:\frac{1}{6}=\frac{1}{15}\cdot6=\frac{6}{15}=\frac{2}{5}\)
\(c,\frac{1}{3}x+\frac{2}{5}(x+1)=0\)
\(\Leftrightarrow\frac{1}{3}x+\frac{2}{5}x+\frac{2}{5}=0\)
\(\Leftrightarrow\frac{11}{15}x=-\frac{2}{5}\)
\(\Leftrightarrow x=-\frac{6}{11}\)
d,e,f Tương tự
a ) \(\left(x-3\right).\left(x+2\right)+\left(x-1\right).\left(x+1\right)-\left(2x-1\right)x\)
\(=x.\left(x+2\right)-3.\left(x+2\right)+x.\left(x+1\right)-1.\left(x+1\right)-\left(2x-1\right)x\)
\(=x^2+2x-3x-6+x^2+x-x-1-2x^2+x\)
\(=-6\)
\(\RightarrowĐPCM\)
\(\left|x+1\right|,\left|x-2\right|,\left|x+3\right|\ge0\)
\(6\ge0\Rightarrow x\ge0\)
\(\left|x+1\right|+\left|x-2\right|+\left|x+3\right|=6\)
\(\Rightarrow\left(x+1\right)+\left(x-2\right)+\left(x+3\right)=6\)
\(\Rightarrow\left(x+x+x\right)+\left(1-2+3\right)=6\)
\(\Rightarrow3x+2=6\)
\(\Rightarrow3x=6-2\)
\(\Rightarrow3x=4\)
\(\Rightarrow x=\frac{4}{3}\)